Analysis of Student Circular Migration Patterns towards Student Organization Culture (Ormawa) at Surabaya State University - Stiawan, Agung; Marzuqi, Muhammad Ilyas; Prastiyono, Hendri (IKIP Widya Darma Surabaya, 2024)
Objective: This research try to identify the condition of circular migration still exist in Surabaya particularly weekly and monthly shuttle migrants and the settled migrants. The research was to examine demographic of the migrant students of State University of Surabaya Campus and their impact on the organizational culture. Furthermore, the study aimed at establishing whether economic characteristics and different demographic factors, to name but employment status of parents, wages, and region of origin of the migrants affected circular migration and joining organizations. Method: In this research, a survey was administered in the year 2023, out of which seven factors were selected under the two broad headings of economic and demographic factors. For descriptive analysis, the probit analysis was performed while for estimation of the impact of the above independent variables, the regression analysis with Stata 10 based on Linear Probability Model (LPW) was conducted. Results: The findings of the result indicated that employment in service sector and urban origin has a positive and significant effect of the participation in circular migration and joining organisations. On the other hand, employment in the industrial sector and parents’ greater distance are factors that inherently reduce this option. Therefore, the last analysis revealed that both parent wages and trade employment have a relatively little impact on organizational membership and migration, but gender does not have such an impact. Novelty: The current work is an effort to unfold some aspects of circular migration which has not received much attention in the existing literature with the focus on the city of Surabaya. It alone focuses on how economic and demography variable, thus employment status of parents and wages, and urban/rural background, moreover influences circular migration and organisational participation of the students at the State University of Surabaya. This study uses more sophisticated method of probit analysis and Linear Probability Model (LPW) to identify the nature of these variables affecting migration behaviour with a clear differentiation between the service sector and the industrial sector, and impact of the population density of urban centres.